MANTRA YOGA: A TOOL FOR A HEALTHY MIND - Jyoti Vaidik; Sunil K. Vaidik; Kavita Sharma (Journal of Biomedical and Pharmaceutical Research, 2020)
Mantra Yoga is a scientific method devised by the Rishis to activate the extrasensory strength centers inside to facilitate the sublime float of crucial non secular currents in this majestic residing device. The wonderful shape, capabilities and complexity of the human body has been the center of deep attention for thousands of scientists, biologists, anatomists and physiologists considering long. Still loads stay unknown, mainly the frame’s exceptional network of nerves, molecular functions, endocrine machine and the mind. In comparison, what has been experienced and recognised approximately the human body and brain by using rigorous yoga-sadhanas appears to be greater thorough and extensive. In the deep country of trance through devout yoga sadhanas, the Rishis, the yogis of the Vedic times, had located this frame a miniature mirrored image of the entire cosmos, as noted within the quote – "Yat Brahmande Tat Pinde". Mantras have terrific significance in the intellectual and non secular evolution of concord. These can also take place excellent results inside the physical international; they could be powerful like a Patton tank or an atomic bomb. Our spiritually empowered, eminent ancestors – the rishis, knew this reality and had consequently advanced a whole gamut of mantras for precise purposes and had also devised the techniques of experimentation with use of those subliminal tools.